2007
DOI: 10.1016/j.ejcts.2006.11.043
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing early and late outcome following the Fontan procedure in the current era. The ‘Two Commandments’?☆

Abstract: Late outcome of the Fontan circulation is encouraging. Ventricular morphology, surgical technique and fenestration do not appear to influence early or late outcome. Preoperatively impaired ventricular function and elevated pulmonary artery pressures have an adverse influence on both early and late outcome. Reintervention is common, with small preoperative pulmonary artery size being an additional risk factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
184
1
11

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 249 publications
(202 citation statements)
references
References 24 publications
6
184
1
11
Order By: Relevance
“…18,19 In our study, one third of patients were alive after 45 years of follow-up, with the majority of patients dying at a young age. The late survival of patients operated from 1953 to 1989 and 1990 to 2009 was comparable until 8 years after the operation; thereafter, the late survival of patients operated on from 1990 to 2009 was significantly higher than that for patients operated on from 1953 to 1989.…”
Section: Survivalmentioning
confidence: 98%
“…18,19 In our study, one third of patients were alive after 45 years of follow-up, with the majority of patients dying at a young age. The late survival of patients operated from 1953 to 1989 and 1990 to 2009 was comparable until 8 years after the operation; thereafter, the late survival of patients operated on from 1990 to 2009 was significantly higher than that for patients operated on from 1953 to 1989.…”
Section: Survivalmentioning
confidence: 98%
“…A recent study with a large cohort indicated the importance of "2 recommendations": that is, pulmonary artery resistance and ventricular function. 6 Other possible relevant risk factors may be atrioventricular valve dysfunction and surgery-related issues, such as a longer cardiopulmonary bypass time. 15 Our results do not contradict the previous reports and the early postoperative hemodynamics, especially a lower CVP and no history of an AVVR repair, emerged as important independent predictors of an excellent status for the next 15 postoperative years.…”
Section: Traditional Risk Factorsmentioning
confidence: 99%
“…2 Although the surgical techniques have evolved, 3,4 the procedure remains palliative with current 10-year survival rates reaching 90%. 5,6 The prevalence of Fontan patients has consequently increased significantly over the past decades, 7 and clinicians are now frequently caring for patients who suffer from a number of late comorbidities, including arrhythmias and exercise intolerance. These problems will continue to rise markedly.…”
Section: Introduction Of the Fontan Operation In 1971mentioning
confidence: 99%